Java data analysis data mining, big data analysis, NoSQL, and data visualization - Hubbard, J. R. 1943- (Packt Publishing, 2017)
If you are a student or Java developer or a budding data scientist who wishes to learn the fundamentals of data analysis and learn to perform data analysis with Java, this book is for you. Some familiarity with elementary statistics and relational databases will be helpful but is not mandatory, to get the most out of this book. A firm understanding of Java is required. This book will help you learn the tools and techniques in Java to conduct data analysis without any hassle. After getting a quick overview of what data science is and the steps involved in the process, you'll learn the statistical data analysis techniques and implement them using the popular Java APIs and libraries. Through practical examples, you will also learn the machine learning concepts such as classification and regression. By the end of this book, you will have a solid understanding of the various data analysis techniques, and how to implement them using Java.
Includes index. - Online resource; title from cover (Safari, viewed October 31, 2017)
Keywords: Java (Computer program language); Java (Computer program language) -- Handbooks, manuals, etc; Relational databases -- Computer programs; Regression analysis -- Computer programs; Data mining; Information visualization; Electronic data processing; Relational databases; Data Mining; Java (Langage de programmation); Java (Langage de programmation); Guides, manuels, etc; Bases de données relationnelles; Logiciels; Exploration de données (Informatique); Visualisation de l'information; Bases de données relationnelles; COMPUTERS; Programming Languages; Java; COMPUTERS; Databases; Data Mining; Relational databases; Computer programs; Regression analysis; Computer programs; handbooks; Handbooks and manuals; Guides et manuels; Handbook